2017
DOI: 10.1002/cbic.201700046
|View full text |Cite
|
Sign up to set email alerts
|

The Lipids of the Early Endosomes: Making Multimodality Work

Abstract: Early endosomes are dynamic intracellular compartments that fuse with incoming endocytic carrier vesicles and associated cargoes from the plasma membrane. It has been long known that the chemical structures of lipids confer striking properties and rich biochemistry on bilayers. Although the organisational principles of the plasma membrane are relatively better understood, understanding endosomal membranes has been challenging. It has become increasingly apparent that endosomal membranes, because of their lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 118 publications
(138 reference statements)
1
7
0
Order By: Relevance
“…Overall, our data suggest that Lgd partially depends upon the early-acting ESCRT complexes for its localization, but it retains an ability to associate with endosomes even in their absence, arguing that additional factors, such as phospholipids that have been suggested to associate with its C2 domain ( Gallagher and Knoblich, 2006 ), are also involved in directing Lgd to these compartments ( Figure 2, A–D ). Consistent with this idea, we found that recombinant Lgd, which forms elongated monomers in solution ( Figure 2E ), binds directly to liposomes in vitro, in a manner that is dependent on the presence of acidic phospholipids, which are abundant in early endosomes ( Figure 2F ; Arumugam and Kaur, 2017 ).…”
Section: Resultssupporting
confidence: 73%
“…Overall, our data suggest that Lgd partially depends upon the early-acting ESCRT complexes for its localization, but it retains an ability to associate with endosomes even in their absence, arguing that additional factors, such as phospholipids that have been suggested to associate with its C2 domain ( Gallagher and Knoblich, 2006 ), are also involved in directing Lgd to these compartments ( Figure 2, A–D ). Consistent with this idea, we found that recombinant Lgd, which forms elongated monomers in solution ( Figure 2E ), binds directly to liposomes in vitro, in a manner that is dependent on the presence of acidic phospholipids, which are abundant in early endosomes ( Figure 2F ; Arumugam and Kaur, 2017 ).…”
Section: Resultssupporting
confidence: 73%
“…Next, we examined whether the difference in activity between complexes I and II could be because complex II, which is normally active on early endosomes, was not assayed on endosome-mimicking membranes. There is evidence that early endosomes are rich in cholesterol and sphingomyelin ( Bissig and Gruenberg, 2013 ; Arumugam and Kaur, 2017 ; Kobayashi et al, 2002 ). Therefore, we measured the activity of complexes I and II in the presence of 10% cholesterol and 10% sphingomyelin ( Figure 1—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In regard to protein-generated curvature, some amphipathic helices (e.g., alfa-synuclein and Sar1), and C2 domains (e.g., Synaptotagmin) insert into membranes to generate membrane curvature [152][153][154][155]. In endocytic pathways, where the lipid composition is similar to that of PM membranes and more tightly packed and less flexible than that of ER membranes [156,157], curvature is generated by several representative proteins, such as sorting nexin (SNX), and endophilin proteins that have BAR domains [158][159][160][161]. In contrast to the ALPS motif, BAR domains not only sense membrane curvature but generate and enhance it (Figure 5B) [162][163][164].…”
Section: Membrane Curvaturementioning
confidence: 99%
“…This condition was purposefully designed to see an exaggerated effect of electrostatics on lipid kinase activities in vitro. As mentioned below (see Section 7.7), PS can be locally enriched in ER membranes, where complex I is recruited during starvation, and has an important role on early endosomes [157], to which complex II and its recruiting protein Rab5 are mainly localized, but it remains elusive whether this activation by 25% DOPS could be physiological or not. In particular, VPS34 alone lacks the membrane-associating adaptor arm (Figure 2B) and was inactive on 10% DOPS-containing GUVs.…”
Section: The Use and Interpretation Of High-percentage Ps In Vitromentioning
confidence: 99%